2015
DOI: 10.6026/97320630011185
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory apparatus of Drosophila larvae

Abstract: Many insects, including Drosophila melanogaster, have a rich repertoire of olfactory behavior. Combination of robust behavioral assays, physiological and molecular tools render D. melanogaster as highly suitable system for olfactory studies. The small number of neurons in the olfactory system of fruit flies, especially the number of sensory neurons in the larval stage, makes the exploration of sensory coding at all stages of its nervous system a potentially tractable goal, which is not possible in the foreseea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Olfaction plays a minor role in larvae. The small number of neurons in the Drosophila olfactory system makes it a very convenient system for olfactory studies (Bose et al, 2015 ), enabling the exploration of sensory coding at all stages of nervous system development (Bose et al, 2015 ). In Drosophila larvae, the epidermal growth factor receptor (Rahn et al, 2013 ) and serotonin signaling (Annina et al, 2017 ) are necessary for learning and memory.…”
Section: Introductionmentioning
confidence: 99%
“…Olfaction plays a minor role in larvae. The small number of neurons in the Drosophila olfactory system makes it a very convenient system for olfactory studies (Bose et al, 2015 ), enabling the exploration of sensory coding at all stages of nervous system development (Bose et al, 2015 ). In Drosophila larvae, the epidermal growth factor receptor (Rahn et al, 2013 ) and serotonin signaling (Annina et al, 2017 ) are necessary for learning and memory.…”
Section: Introductionmentioning
confidence: 99%
“…In insects, homonymous structures are responsible for temporal integration of sensory signals; they mediate learning and memory processes and receive olfactory input from the antennal lobes ( de Belle and Heisenberg, 1994 ; Schürmann, 1995 ; Heisenberg, 1998 ). In fact, it has been shown that the mushroom bodies of Drosophila melanogaster play a key role in associative learning of olfactory information ( Laurent and Naraghi, 1994 ; Bose et al, 2015 ). In the honeybee Apis mellifera and fruitfly D. melanogaster olfactory sensory neurons with olfactory receptors are present in the antenna and converge into a few glomeruli in the antennal lobe and synapse with specific second-order neurons, especially the mushroom bodies ( Tanaka et al, 2004 ; Kirschner et al, 2006 ; Zube et al, 2008 ; Galizia and Rössler, 2010 ; Ramdya and Benton, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In D. melanogaster larvae, the olfactory system is mainly localized to the head region. The head portion of larvae has a couple of DOs expressing 21 OSNs in each [3,4] (Figure 1A). Contrarily, the adult fruit flies detect odorants through a pair of antennae and maxillary palps (Figure 1B).…”
Section: Olfactory System-components and Basic Organizationmentioning
confidence: 99%
“…At larval stage, the antennal nerve (AN) connects 21 OSNs in DO to the larval antennal lobe (LAL). The LAL has about 30 subunits comparable to the glomerulus of an adult fly [4,45]. The sensory information from LAL then goes through several projections and local neurons (PNs & LNs) to be relayed to higher centers of the larval brain to initiate a behavioral response (Figure 3A).…”
Section: Olfactory System-components and Basic Organizationmentioning
confidence: 99%
See 1 more Smart Citation